Time to rethink the ECA (Revista do Tribunal Regional Federal da 3ª Região, 2010)
On this 20th anniversary of the introduction of the Statute of the Child and Adolescent (ECA) into our legislation, it seems to us, in the light of all the indicative evidence, that it is high time to rethink this innovative - but at the same time absolutely ineffective - piece of legislation, within the context of the very negative results that have been observed (and particularly verified) so far. Although it is clear to recognize - in a highly opinionated sense - the existence of a veritable battalion of sociologist judges, ardent and passionate defenders of the ECA, we urgently need to get away from all the passion that naturally surrounds the subject in order to logically establish a true and impartial vision, It is not difficult to deduce that, to a large extent, it was the naive attempt to implement a “Swiss Code” in a tropical country (in synergistic defiance of our actual reality) - more than any other single factor - that led to the absurd extremes that we are compelled to experience on a daily basis.
Keywords: Statute of the Child and Adolescent; critical view; minority; impunity